Processo de legitimação artística – reflexões acerca de instituições museológicas de arte contemporânea do Brasil (MAC-USP) e da Argentina (MALBA) - Oliveira, Elisangela Cardoso Hernandes e (Universidade de São Paulo | Escola de Comunicações e Artes, 2010)
This article proposes a comparative analysis between the Museum of Contemporary Art, University of São Paulo (MAC-USP), Brazil, and the Museo de Arte Latinoamericano de Buenos Aires (MALBA), Argentina, both museums of contemporary art, with the objective of study the process of legitimation and artists and works in the museum institutions, by taking the historical period from 2006 to 2008.